1996
DOI: 10.1097/00006842-199605000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Verbal and Nonverbal Emotion Recognition in Alexithymia

Abstract: Although clinical observations suggest that alexithymic individuals have a deficit in their ability to recognize emotional stimuli and that this deficit is not simply due to a problem in verbal labeling, these two hypotheses have not been empirically confirmed. Three hundred eighty participants in a community survey without current or past histories of psychiatric disorder completed two independent measures of alexithymia [the Levels of Emotional Awareness Scale (LEAS) and the Toronto Alexithymia Scale (TAS-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
333
6
12

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 447 publications
(383 citation statements)
references
References 32 publications
27
333
6
12
Order By: Relevance
“…Our results are consistent with previous studies in which authors have presented images of facial expressions taken from FACS (Allerdings, 1997;Lane et al, 1996Lane et al, , 2000McDonald & Prkachin, 1990;Mann et al, 1994;Pandey & Mandal, 1997;Parker et al, 2005;Prkachin et al, 2009;Reker et al, 2010), as well as those who have had facial micro-expressions (Swart, Kortekeer, & German, 2009), and degraded presentations of facial expressions that hinder its recognition (KĂ€tsyri et al, 2008). On the other hand, studies using the affective priming task (Suslow, 1998;Suslow & Junghanns, 2001;Suslow et al, 2001) have showed inconsistent results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with previous studies in which authors have presented images of facial expressions taken from FACS (Allerdings, 1997;Lane et al, 1996Lane et al, , 2000McDonald & Prkachin, 1990;Mann et al, 1994;Pandey & Mandal, 1997;Parker et al, 2005;Prkachin et al, 2009;Reker et al, 2010), as well as those who have had facial micro-expressions (Swart, Kortekeer, & German, 2009), and degraded presentations of facial expressions that hinder its recognition (KĂ€tsyri et al, 2008). On the other hand, studies using the affective priming task (Suslow, 1998;Suslow & Junghanns, 2001;Suslow et al, 2001) have showed inconsistent results.…”
Section: Discussionsupporting
confidence: 92%
“…In this line, previous studies have shown a significant correlation between alexithymia and a lack of ability to recognize emotions in photographs of facial expressions (Allerdings, 1997;Lane et al, 1996Lane et al, , 2000Mann, Wise, Trinidad, & Kohanski, 1994;McDonald & Prkachin, 1990;Pandey & Mandal, 1997;Parker et al, 1993;Parker, Prkachin, & Prkachin, 2005;Prkachin, Casey, & Prkachin, 2009). These deficits have been found with tasks in which participants were required to reply in a very short period of time (Pedrosa et al, 2009), as well as in those with masked stimuli to make it difficult to recognize them (Kugel et al, 2008;Reker et al, 2010), and with static emotional stimuli, such as FACS, and dynamic videos (KĂ€tsyri, Saalasti, Tiippana, von Wendt, & Sams, 2008;Ridout, Thomas, & Wallis, 2010) (for a review, see Grynberg et al, 2012).…”
mentioning
confidence: 78%
“…Studies have shown that people with alexithymia have difficulty in identifying the emotion of others from their face (e.g., Lane et al, 1996). Recognizing emotions play an important role on interpersonal relations.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, impaired representation of the emotional state of the self in alexithymia would lead to impaired representation of the other's emotion, which may be manifested as impaired recognition of emotion. Several studies support this conjecture, reporting impaired recognition of facial emotion in alexithymia (Mann et al 1994;Parker et al 1993;Jessimer and Markham 1997;Lane et al 1996Lane et al , 2000Prkachin et al 2009). The reliance of accurate emotion recognition on typical visual scan paths to emotional face stimuli (Aviezer et al 2008;Calder et al 2000;Smith et al 2005;Wong et al 2005), makes it possible that the impaired emotion recognition in individuals with alexithymia is due to atypical attention to the eye and mouth regions of emotional face stimuli.…”
mentioning
confidence: 89%